Simultaneous aorto - iliac and femoro - popliteal revascularization: Indicaciones, técnica y resultados - Danza, Rómulo; Olivera, Daniel; Baldizán, Jorge; Grillo, Bartolomé (Cirugía del Uruguay, 1979)
Isolated proximal or distal revascuiarization is insufficient for solving the problem of arteriopathies of lower limbs, in a considerable number of patients. Hence we find associated surgery, generally performed in two stages. In sorne special cases Simultaneous Revascularization (SR) may be indicated.